Engaging in a Secularized Public Sphere – a Possible Qur’anic Perspective? - Rahman, Sara (Journal of empirical theology, 2023)
However, it remains an open question to what extent religious citizens in plural societies can or want to participate in such a communication process based on their religious self-understanding. In this article, an attempt will be made to investigate this question, at least within the Islamic faith tradition. A Qur’anic narrative will be examined for possible indications of how the Qur’an conceives communication with those of different worldviews. The analyzed narrative reveals perspectives of understanding from which remarkable contributions to social cohesion can be derived.